Beneficial Effects of Pomegranate Peel Extract and Probiotics on Pre-adipocyte Differentiation - Sorrenti, Valeria; Randazzo, Cinzia Lucia; Caggia, Cinzia; Ballistreri, Gabriele; Romeo, Flora Valeria; Fabroni, Simona; Timpanaro, Nicolina; Raffaele, Marco; Vanella, Luca (Frontiers in Microbiology, 2019)
Pomegranate is a fruit of great interest for its multiple beneficial effects on human health thanks to the ellagitannins and anthocyanins content, which are protective towards a wide variety of diseases including inflammatory diseases. Many investigators have reported that pomegranate waste (peel and seeds) extracts, made from waste product of industrial processing, show free radical scavenger and a potent antioxidant capacity. Pomegranate extracts (PE) were also reported to possess noteworty antibacterial, antiviral, hypolipidemic and anti-inflammatory bioactivities. These potential health benefits are attributed to the polyphenolic compounds content, which includes punicalagins, gallic acid, and ellagic acid derivatives. Pomegranate ellagitannins are hydrolyzed by gut microbiota to smaller phenolics, such as ellagic acid. Ellagic acid is then absorbed into the blood circulation, while ellagitannins are not absorbed and are metabolized into urolithins. The focus of the present manuscript was to study the prebiotic potentiality of a PE, soluble in water, and characterized through UPLC-PDA-ESI/MSn for its phenolic and anthocyanin content. The extract showed antioxidant activities in a concentration dependent manner for the DPPH scavenging assay. Since a number of probiotic strains have been shown to affect adipogenesis in cell culture, this study was performed to test the in vitro effects of PE and probiotic L. rhamnosus GG ATCC 53103 strain (LGG) on 3T3-L1 cell line. PE and probiotics substantially reduced the triglyceride content and intracellular lipid increase, compared to the control group. However, the combination treatment of PE and LGG-FSB was the most effective in reducing triglyceride content and intracellular lipid accumulation. The mRNA expression levels of the main transcriptional factors implicated in adipocyte differentiation were substantially lower in 3T3-L1 cells treated with PE and LGG-FSB. These results evidenced that probiotics and polyphenols contained in PE may affect in vitro adipogenesis and may contribute in development of new nutraceutical/probiotic-based remedies to prevent and to treat obesity.